The Role of The Police in Disclosing Cases of Motorcycle Theft at Medan City Police Station - Panggabean, Denny Boy; Isnaini; Suhaidi (JURNAL MERCATORIA, 2024)
This article aims to handle motorcycle theft in the jurisdiction of the Medan City Police and its surrounding areas. The purpose of this study is to examine and analyze the role of the Indonesian National Police in revealing motorcycle theft cases. The problem is focused on maintaining public security and order, law enforcement, protection, shelter and service to the community. This type of research uses normative legal research, meaning that this study tends to use secondary data, both primary legal materials and secondary legal materials. Data were collected using document studies and analyzed. Analysis for qualitative data was carried out by selecting articles containing legal principles. This study concludes that the Role of the Indonesian National Police in revealing motorcycle theft cases in the jurisdiction of the Medan City Police and its surrounding areas & Obstacles to the Indonesian National Police in providing security protection to motorized vehicle users occur due to 2 factors, namely legal factors and non-legal factors.